Correlation of Zn2+ content with aflatoxin content of corn. - Failla, L J (1986)
Forty-nine samples from the 1983 Virginia corn harvest were analyzed for aflatoxin, zinc, copper, iron, and manganese content. Values (mean +/- standard deviation) were as follows: aflatoxin, 117 +/- 360 micrograms/kg; zinc, 22.5 +/- 3.4 mg/kg; copper, 2.27 +/- 0.56 mg/kg; iron, 40.8 +/- 18.7 mg/kg; and manganese, 5.1 +/- 1.1 mg/kg. Aflatoxin levels positively correlated with zinc (Spearman correlation coefficient, 0.385; P less than 0.006) and copper levels (Spearman correlation coefficient, 0.573; P less than 0.0001). Based on biochemical data in the literature, we believe that the correlation with zinc is important and that there may be a cause-and-effect relationship between zinc levels in corn and aflatoxin levels which are produced upon infection with Aspergillus flavus or A. parasiticus. Control of aflatoxin contamination in field corn by decreasing the zinc levels may be feasible, but no methods to decrease zinc levels are currently available.